Fast and easy preparation of few-layered-graphene/magnesia powders for strong, hard and electrically conducting composites. (September 2018) - Weibel, Alicia; Mesguich, David; Chevallier, Geoffroy; Flahaut, Emmanuel; Laurent, Christophe
Abstract: Composite powders were prepared by the chemical vapor deposition (CH4 /Ar atmosphere) of carbon in the form of 2–8 layers few-layered-graphene (FLG) covering the MgO powder grains, without any mixing step. The composites were consolidated to nearly full (99%) density by spark plasma sintering with no or little damage to the FLG. The FLG is located along the MgO grain boundaries, as opposed to be dispersed as discrete particles or flakes. This causes a dramatic hindrance of the MgO grain growth, the average grain size being considerably lower for the sample with 2.08 vol% carbon (200 nm) than for pure MgO (3.7 μm). The samples are investigated by Raman spectroscopy, scanning and transmission electron microscopy. The composites are electrically conducting with a percolation threshold below 0.56 vol%. Compared to pure MgO, the composites are simultaneously stronger (345 vs 200 MPa) and harder (9.8 vs 3.8 GPa). This could arise from reinforcement mechanisms such as crack-deflection and crack-bridging by FLG, but also from MgO grain refinement. Graphical abstract: Image 1